Conceptual design: A search space - Gushchin, Alexander; Divakova, Marina (project baikal, 2025)
The authors show that project and scientific activities have an antinomic relationship. The project requires going deeper into the singular, and the result of the project is unique. The scientific activity requires generalization of particular (single) results, and the result is universal. This paradigm allows us to formalize the concept of the “search space for design solutions”. The authors formalize the structure of the search space for conceptual solutions using the concept of constructs introduced by the Soviet philosopher and logician S. P. Nikanorov. Constructs are a universal language for design patterns.
Keywords: project activity; scientific activity; conceptual project; construct; search space for design solutions